2019
DOI: 10.29309/tpmj/2019.26.04.3353
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Diseases in Madina Region;

Abstract: Objectives: The study is designed to get useful information and epidemiological data for clinical practice and investigations regarding glomerular disease frequencies in Madina region.  Study Design & Setting: Single-center retrospective study at King Fahd Hospital Madina. Period: 01 year (March 2016- March 2017). Methods: All native renal biopsies were studied for the period of 1 year (March 2016- March 2017). Only glomerular disease patterns were analyzed. The diagnosis of each case was based on histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…This nding is consistent with other studies in Egypt [16,27] and also in Iraq [28] and Oman [29]. This nding is also similar to previous reports in Saudi Arabia [5,30,31], although a recent Saudi study showed that membranous nephropathy (MN) was the most common primary GD [21]. It might be possible that the latter study indicates a changing spectrum of GDs in Saudi Arabia; a notion that awaits con rmation by future research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This nding is consistent with other studies in Egypt [16,27] and also in Iraq [28] and Oman [29]. This nding is also similar to previous reports in Saudi Arabia [5,30,31], although a recent Saudi study showed that membranous nephropathy (MN) was the most common primary GD [21]. It might be possible that the latter study indicates a changing spectrum of GDs in Saudi Arabia; a notion that awaits con rmation by future research.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, many other published studies showed predominance of primary GDs, whether these studies were carried out in Egypt [15,17] or other countries, e.g. Saudi Arabia [5,21], Taiwan [22] and Bangladesh [23]. The reason for this discrepancy in the frequency of secondary in comparison to primary GDs is not readily explainable; but one possible explanation might reside in misclassi cation of some secondary GDs as primary due to lack of the ability to identify the accompanying disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is consistent with other studies in Egypt [16,27] and also in Iraq [28] and Oman [29]. This nding is also similar to previous reports in Saudi Arabia [5,30,31], although a recent Saudi study showed that membranous nephropathy (MN) was the most common primary GD [21]. It might be possible that the latter study indicates a changing spectrum of GDs in Saudi Arabia; a notion that awaits con rmation by future research.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, many other published studies showed predominance of primary GDs, whether these studies were carried out in Egypt [15,17] or other countries, e.g. Saudi Arabia [5,21], Taiwan [22] and Bangladesh [23]. The reason for this discrepancy in the frequency of secondary in comparison to primary GDs is not readily explainable; but one possible explanation might reside in misclassi cation of some secondary GDs as primary due to lack of the ability to identify the accompanying disorder.…”
Section: Discussionmentioning
confidence: 99%